The end of Modernism : Elias Canetti's Auto-da-fé - Donahue, William Collins (University of North Carolina studies in the Germanic languages and literatures ;, 2001)
A study of Elias Canetti's "Auto-da-Fe (Die Blendung)", placing the work in its cultural and philosophical contexts. It situates the novel not only in relation to Canetti's body of social thought, but also within debates on Freud, misogyny, racial anti-semitism, the failure of humanism, and more